NILAI KARAKTER DARI DONGENG ANAK PADA MAJALAH BOBO DAN IMPLEMENTASINYA DI MASA PANDEMI COVID-19 - Masyithah Maghfirah Rizam (Program Studi PGSD Universitas Flores, 2021)
Children's fairy tales are a literary art that presents children's favorite entertainment and there is knowledge to increase children's knowledge. Children's fairy tales are a way to instill five main values in strengthening character education. It must be known, namely religious values, nationalism, integrity, independence, and mutual cooperation. This research was a qualitative research by describing the five main values of character education in the children’s fairy tale on bobo.grid.id and its implementation in learning during the Covid-19 pandemic. The researcher as the key instrument carried out heuristic and hermeneutic readings to find and describe the main values of character education, namely religious, nationalist, integrity, independent, and mutual cooperation values in Bobo children's fairy tales. The results show that there are five main values of character education in children's fairy tales on bobo.grid.id that can be implemented in learning during the Covid-19 pandemic such as praying to God so that the pandemic will end soon and protocols comply with the safety of self and others.